COVID-19 Impact on Modern Virtual Pathology Education: Challenges and Opportunities - Seyed Esmaeil Azimi Khatibani; Shima Tabatabai (Iranian Society of Pathology, 2021)
Background & Objective: Pathology education conventional methods have been disrupted by the Corona-Virus Disease 2019 (COVID-19) outbreak, compelling a re-evaluation of the means of educational interactions from the undergraduate to the postgraduate level. This commentary explores how the COVID-19 outbreak has challenged pathology education.Methods: We reviewed the current challenges and determined the potential implications of virtual technologies on modern pathology education for the future of pathology competency learning and assessment.Results & Conclusion: The challenges are partly due to transferring from in-person teaching to a virtual education. Other reasons are shifting away from discipline-based teaching to organ-system based in medical curriculum and additional pressures on pathology faculties, such as increased demand for pathology services, lack of time, and learning resources. Keeping the national standards in pathology education even in the constant disruptions from pandemic outbreaks are current challenges. Pathology expertise will need to use emergent technologies in providing educational material to ensure quality pathology education. However, virtualization of pathology education produces a value of digital pathology and web-based pathology training materials. Medical students could review clinical cases remotely with their supervisors and gain the pathology competencies necessary for clinical practice.We need new innovative strategies, and we suggested the following steps to take advantage of the current opportunity to meet the challenges: evaluating the available digital training materials for formal pathology education, investing in the virtual infrastructure for competency-based pathology education, expanding student/residents exposure to pathology educational cases through virtual platforms; applying digital pathology solutions for virtual pathology education.